ANALISIS HUBUNGAN ANTARA KEKUATAN IKLAN HONDA VERSI ONEHEART TERHADAP KEKUATAN RESPONS KONSUMEN BERDASARKAN METODE CUSTOMER RESPONSE STRENGTH - Trias Aprilianto Nugroho; Herni Justiana Astuti (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2014)
This study aims to analyze the correlation the strength of the advertisement Honda One Heart version with the strength of consumer respons student of University Muhammadiyah Purwokerto based by Customer Response Strength (CRS) Methods. Customer Response Strength (CRS) Methods was the one of the measurement methods of the consumer respons to advertisement.The strength of consumer’s respons to the advertisement was measured a phase the AIDCA (Attention, Interest, Desire, Conviction an Action) consumer towards the presentation of the advertising. Whereas the strength of the advertisement by a phase of frequency of the consumer saw the advertisement and the consumer’s response on the attraction of the advertisement. The result of the research that indicate a correlation the strength of the advertisement Honda One Heart version with the strength of customer respons at 100 repondents in category strength enough.This is evidenced from value of 0,51 calculated r in interval 0,41 to 0,60. Whit the result that Honda need to more a considered to for over a frequence in marketing product so that a consumers response toward a brand of Honda gain strength. Key words: A Strength of Advertisement, A Strength of Consumer Respons, and AIDCA(Attention, Interest, Desire, Conviction and Action)